The effects of financial incentives for case finding for depression in patients with diabetes and coronary heart disease: interrupted time series analysis - McLintock, Kate (BMJ Publishing Group, 2014)
OBJECTIVE: To evaluate the effects of Quality and Outcomes Framework (QOF) incentivised case finding for depression on diagnosis and treatment in targeted and non-targeted long-term conditions. DESIGN: Interrupted time series analysis. SETTING: General practices in Leeds, UK. PARTICIPANTS: 65 (58%) of 112 general practices shared data on 37 229 patients with diabetes and coronary heart disease targeted by case finding incentives, and 101 008 patients with four other long-term conditions not targeted (hypertension, epilepsy, chronic obstructive pulmonary disease and asthma). INTERVENTION: Incentivised case finding for depression using two standard screening questions. MAIN OUTCOME MEASURES: Clinical codes indicating new depression-related diagnoses and new prescriptions of antidepressants. We extracted routinely recorded data from February 2002 through April 2012. The number of new diagnoses and prescriptions for those on registers was modelled with a binomial regression, which provided the strength of associations between time periods and their rates. RESULTS: New diagnoses of depression increased from 21 to 94/100 000 per month in targeted patients between the periods 2002–2004 and 2007–2011 (OR 2.09; 1.92 to 2.27). The rate increased from 27 to 77/100 000 per month in non-targeted patients (OR 1.53; 1.46 to 1.62). The slopes in prescribing for both groups flattened to zero immediately after QOF was introduced but before incentivised case finding (p<0.01 for both). Antidepressant prescribing in targeted patients returned to the pre-QOF secular upward trend (Wald test for equivalence of slope, z=0.73, p=0.47); the slope was less steep for non-targeted patients (z=−4.14, p<0.01). CONCLUSIONS: Incentivised case finding increased new depression-related diagnoses. The establishment of QOF disrupted rising trends in new prescriptions of antidepressants, which resumed following the introduction of incentivised case finding. Prescribing trends are of concern given that they may include people with mild-to-moderate depression unlikely to respond to such treatment.